The impact of the COVID-19 lockdown on elite sportswomen. Issue 6 (2nd November 2022) - Bowes, Ali; Lomax, Lucy; Piasecki, Jessica
ABSTRACT: Research question: The COVID-19 pandemic decimated elite level sport across the globe, although there were concerns that this impact affected women's sport much more so than for men's sport. This research considers the impact of the enforced global lockdown on elite women athletes, examining the immediate effect on their training practices, welfare and financial situation. Methods: A qualitative, online survey was used to collect anonymous data from 95 elite sportswomen. Data were coded to enable frequency analysis, and then analysed thematically. Results: Many sportswomen noted the positive support received from coaching networks regarding adapted, individualised training programmes and their mental well-being. A reduction in time spent training, and changes to types of training, was reported. However, many felt they had less access to equipment as women, and that men's sport was a priority. Professional and semi-professional sportswomen, already operating in financially precarious circumstances, were also impacted through a reduction in match fees and/or sponsorship, or furlough. Implications: The findings provide empirical evidence of a gendered dimension to the experiences of elite athletes during lockdown. When elite sport re-builds post-COVID, there should be a greater awareness of the difficulties faced by sportswomen, and targeted action to tackle gender inequality in sport.